Preliminary analysis of Psoroptes ovis transcriptome in different developmental stages. Issue 1 (December 2016) - He, Man-Li; Xu, Jing; He, Ran; Shen, Neng-Xing; Gu, Xiao-Bin; Peng, Xue-Rong; Yang, Guang-You
Abstract Background Psoroptic mange is a chronic, refractory, contagious and infectious disease mainly caused by the mange mitePsoroptes ovis, which can infect horses, sheep, buffaloes, rabbits, other domestic animals, deer, wild camels, foxes, minks, lemurs, alpacas, elks and other wild animals. Features of the disease include intense pruritus and dermatitis, depilation and hyperkeratosis, which ultimately result in emaciation or death caused by secondary bacterial infections. The infestation is usually transmitted by close contact between animals. Psoroptic mange is widespread in the world. In this paper, the transcriptome ofP. ovis is described following sequencing and analysis of transcripts from samples of larvae (i.e. the Pso_L group) and nymphs and adults (i.e. the Pso_N_A group). The study describes differentially expressed genes (DEGs) and genes encoding allergens, which help understanding the biology ofP. ovis and lay foundations for the development of vaccine antigens and drug target screening. Methods The transcriptome ofP. ovis was assembled and analyzed using bioinformatic tools. The unigenes ofP. ovis from each developmental stage and the unigenes differentially between developmental stages were compared with allergen protein sequences contained in the allergen database website to predict potential allergens. Results We identified 38, 836 unigenes, whose mean length was 825 bp. On the basis of sequence similarity with seven databases, a total of 17, 366 unigenes were annotated. A total of 1, 316 DEGs were identified, including 496 upregulated and 820 downregulated in the Pso_L group compared with the Pso_N_A group. We predicted 205 allergens genes in the two developmental stages similar to genes from other mites and ticks, of these, 14 were among the upregulated DEGs and 26 among the downregulated DEGs. Conclusion This study provides a reference transcriptome ofP. ovis in absence of a reference genome. The analysis of DEGs and putative allergen genes may lay the foundation for studies of functional genomics, immunity and gene expression profiles of this parasitic mite species.